Study and evaluation of physical activity of youth from the Visegrad countries in relation to the WHO recommendations - Ewelina Niźnikowska; Józef Bergier; Barbara Bergier; Michał Bergier; Pongrăc Ăcs; Jăn Junger (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. In recent years, the subject literature has provided concrete recommendations concerning health with regard to specific parameters. Therefore, it is necessary to indicate appropriate physical activity standards for proper development at various stages of human ontogenesis. Objective. The aim of the work was knowledge of the level of physical activity of high school youth in the Visegrad countries, including gender indications, to demonstrate whether the WHO recommendations are fulfilled. Material and methods. The research was conducted in students from four Visegrad countries: the Czech Republic, Poland, Slovakia and Hungary. As the research method, the International Physical Activity Questionnaire − IPAQ in the extended version was used. Results. Boys seem to do much better and have largely fulfilled the WHO recommendation for high-intensity efforts performed 3 times for 20 minutes, and medium and high efforts − 7 times for 60 minutes, which is particularly crucial for the effectiveness of the level of physical activity. Conclusions. It is indispensable to continue monitoring the physical activity of young people using modern research techniques. It seems intentional to intensify promotion and educational activities, which should be aimed at motivating young people to undertake physical activity in accordance with world-wide recommendations.